2021
DOI: 10.1016/j.cub.2021.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Increased LRRK2 kinase activity alters neuronal autophagy by disrupting the axonal transport of autophagosomes

Abstract: Parkinson's disease-causing mutations in the leucine-rich repeat kinase 2 (LRRK2) gene hyperactivate LRRK2 kinase activity and cause increased phosphorylation of Rab GTPases, important regulators of intracellular trafficking. We found that the most common LRRK2 mutation, LRRK2-G2019S, dramatically reduces the processivity of autophagosome transport in neurons in a kinase-dependent manner. This effect was consistent across an overexpression model, neurons from a G2019S knockin mouse, and human induced pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
144
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(169 citation statements)
references
References 89 publications
13
144
2
2
Order By: Relevance
“…LRRK2 also plays a role in trafficking and may influence mitophagosome travel to lysosomes. Previous work has shown that LRRK2 activity can influence phagosome trafficking to lysosomes ( Härtlova et al, 2018 ) and recently it was shown that LRRK2 can influence axonal autophagosome trafficking via the motor adaptor protein JIP4 ( Boecker et al, 2021 ). Relatedly and also of relevance, LRRK2 regulation of JIP4 has been implicated in lysosome tubulation ( Bonet-Ponce et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 also plays a role in trafficking and may influence mitophagosome travel to lysosomes. Previous work has shown that LRRK2 activity can influence phagosome trafficking to lysosomes ( Härtlova et al, 2018 ) and recently it was shown that LRRK2 can influence axonal autophagosome trafficking via the motor adaptor protein JIP4 ( Boecker et al, 2021 ). Relatedly and also of relevance, LRRK2 regulation of JIP4 has been implicated in lysosome tubulation ( Bonet-Ponce et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phafin2 does not interact with JIP3, nor does Phafin1 bind to JIP4. This is important to note, since several other studies have proposed that JIP3 and JIP4 have overlapping functions, and some phenotypes are reported under double knockdown or knockout conditions (Boecker et al, 2021;Gowrishankar et al, 2020;Marchesin et al, 2015;Sato et al, 2015;Vilela et al, 2019b;Williamson & Donaldson, 2019). In comparative structural and biochemical analysis, the similarity of the first two coiled-coil regions has been noted (Isabet et al, 2009;Williamson & Donaldson, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with these observations, the Holzbaur lab has recently reported a LRRK2 kinasedependent recruitment of JIP4 (but not JIP3) to autophagosomes that results in increased kinesin heavy chain (KHC) recruitment in mouse and human neuronal models. As a result, autophagosomes from G2019S expressing neurons show less efficient retrograde transport [64]. JIP4, probably due to its ability to bind to motor proteins (kinesins and dynein) [65], contributes to the formation of a sorting tubule that develops from the lysosome and lacks LRRK2, RAB35 and typical lysosomal membrane markers.…”
Section: Accepted Articlementioning
confidence: 99%
“…JIP4 binds to pRAB10 in the lysosomal surface [59] or the autophagosomal membrane [64]. This model suggests that the phosphorylation of the RABs by LRRK2 has a dual effect, to maintain the RABs in the membrane and to facilitate the interaction with effectors including RILPL1 and JIP4.…”
Section: Accepted Articlementioning
confidence: 99%